Study on the Physical and Mechanical Properties of Ancient Clay Brick Samples of Kathmandu Valley, Nepal - Bhattarai, Jagadeesh; Ghale, Dol Bahadur; Chapagain, Yagya Prasad; Bohara, Narendra Bahadur; Duwal, Nijan (Tribhuvan University Journal, 2018)
Physical and mechanical properties of seven ancient clay brick samples of Kathmandu valley consisting of quartz, feldspars, spinel, margarite, muscovite type of mica mineral and hematite were studied using ASTM standards. All the brick samples used in this study have the water absorption, apparent porosity and bulk density in the range of 10-28 percent, 17-33 percent and 1.2-1.8 g/cm3, respectively, while the compressive strength of all the brick samples is found to be in the range of 5-23 MPa. The bulk density of the tile samples is found to be increased with decreasing the water absorption and apparent porosity. The compressive strength of all the clay brick samples can be correlated with their physical properties. Consequently, durability of the ancient bricks is directly influenced by their physical properties of water absorption, apparent porosity and bulk density.